Managing the high-production herd. V. Challenges of the 90's - John E. Shirley (Kansas Agricultural Experiment Station Research Reports, 1990)
The decade of the 1980s was a transition period for the Dairy Industry in the United States. The decade began with a large milk surplus and low prices and ended with milk shortages and record high prices. The dairy industry experienced drastic governmental action through the milk set-aside and whole herd buy-out programs instituted to reduce the milk surplus and the establishment of the National Dairy Board accompanied by a check-off program to fund advertising and research. The decade ended with a butter surplus and moves by marketing agencies to lower or drop premiums for fat and install premiums for milk protein or solids-not-fat.; Dairy Day, 1990, Kansas State University, Manhattan, KS, 1990; The 1990 Annual KSU Dairy Day is known as Dairy Day, 1990
Keywords: Dairy Day; 1990; Kansas Agricultural Experiment Station contribution; no. 91-148-S; Report of progress (Kansas Agricultural Experiment Station); 608; High-production herd; Dairy; Challenges